Postoperative Complications Causing Readmission in 30 Days after Total Knee Arthroplasty: A Retrospective Nested Case-Control Study of Risk Factors Based on Propensity Score Matching - Tang, Haozheng; Li, Hui; Zhang, Shutao; Wang, You; Qu, Xinhua; Yue, Bing (The Journal of Knee Surgery, 2019)
We performed this study to identify independent risk factors for life-threatening postoperative complications causing 30-day readmissions after total knee arthroplasty (TKA). Improved understanding of these risks may improve efficiency and safety of treatment. We performed a retrospective, nested case-control study using an open-access database of 2,622 patients who underwent primary TKA at a tertiary academic medical center in Singapore between January 2013 and June 2014. Patients were grouped according to the incidence of complications. Multivariate logistic analysis was performed to identify predictive factors for TKA complications. The incidence of postoperative complications was 1.72%. Compared with cases performed with an operative time < 70 minutes, increased operative time was associated with a higher risk of complications. Case duration > 90 minutes was associated with an increased risk (adjusted odds ratio [aOR] = 4.57, p = 0.001; case duration ≥ 111 minutes, aOR = 4.64, p = 0.04; and case duration between 91 and 110 minutes, aOR = 3.20, p = 0.03). The correlation between operative time and complications was nonlinear. Cerebrovascular accident (CVA) or transient ischemic attack (TIA) was an independent risk factor for increased complication rate (aOR = 11.59, p = 0.02). Operative duration has been identified as an independent risk factor for complications after TKA. As it remains a modifiable factor to which doctors are interested in bringing quality improvement, the risk of postoperative complications will be reduced by minimizing the operative duration.
Keywords: total knee arthroplasty (TKA); postoperative complication; operative duration; retrospective nested case-control study; propensity score matching (PSM)